Data from Geant4 calculations of average gamma heating from selected cases of used light water reactor nuclear fuel assemblies in a KBS-3 type deep geological repository - Jansson, Peter (Uppsala University, 2021)
Monte Carlo calculations, using the Geant4 framework version 10.02 [1], of energy deposition from gamma radiation emitted from light water reator fuel assemblies in a KBS-3 type deep geological repository for used nuclear fuel has been performed. Selected cases of boiling and pressurized reactor fuel assemblies from the "SKB-50" set of fuel assemblies were used; "BWR1", "BWR6" and "PWR8" [2]. An isotropic source of gamma-rays with energies of 444, 662, 723 and 1274 keV, depending of the case, were distributed homogeneously in the intersection of a (mid-)plane perpendicular to the canister central axis with all the fuel rods in all fuel assemblies in the canister. The average energy deposition in a 3-dimensional (x,y,z) mesh with 1 cm resolution was calculated per emitted gamma particle. This dataset contains the resulting meshed energy deposition data.

Description of files:
- The gzip compressed tar file contains comma-separated-values (CSV) files with the data "mesh x position [cm], mesh y position [cm], mesh z position [cm], average energy deposition per emitted gamma [MeV]" supplied on each row. The name of the CSV file specifies the fuel assembly id from the SKB-50 set of fuel assemblies as well as the energy of the emitted gamma radiation.
- The txt-file contains the SHA-256 checksum of the gzip compressed tar file.

The dataset was originally published in DiVA and moved to SND in 2024.

Se engelsk version av denna katalogpost för beskrivning.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Data from Geant4 calculations of average gamma heating from selected cases of used light water reactor nuclear fuel assemblies in a KBS-3 type deep geological repository
Keywords: Physics with specialization in Applied Nuclear Physics; Physics with specialization in Applied Nuclear Physics; energy deposition; energy deposition; KBS-3; KBS-3; Geant4; Geant4; nuclear fuel; nuclear fuel; gamma; gamma; Subatomic Physics; Subatomär fysik